2010
DOI: 10.1158/0008-5472.can-10-0007
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Reactive Oxygen Species–Generating Capacity Contributes to the Enhanced Cell Growth of Arsenic-Transformed Epithelial Cells

Abstract: Reactive oxygen species (ROS) have been implicated in the activation of protein kinases, DNA damage responses, and cell apoptosis. The details of how ROS regulate these intracellular biochemical and genetic processes remain to be fully understood. By establishing transformed bronchial epithelial cells through chronic low-dose arsenic treatment, we showed that the capacity of ROS generation induced by arsenic is substantially reduced in the transformed cells relative to the nontransformed cells. Such a reductio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
73
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 56 publications
(81 citation statements)
references
References 30 publications
(33 reference statements)
6
73
2
Order By: Relevance
“…Cigarette smoke, As 3ϩ -contaminated food, and As 3ϩ -contaminated water are non-occupational sources of human exposure to As 3ϩ (22). Our previous study has shown that chronic exposure of human bronchial epithelial cells to As 3ϩ generates ROS and that ROS are responsible for As 3ϩ -induced transformation of these cells (16). In our present study, we have shown that As 3ϩ -transformed cells have a low level of ROS along with highly expressed antiapoptotic proteins (Bcl-2 and Bcl-xL) and antioxidant enzymes (catalase and SOD2) as well as Nrf2 and p62.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Cigarette smoke, As 3ϩ -contaminated food, and As 3ϩ -contaminated water are non-occupational sources of human exposure to As 3ϩ (22). Our previous study has shown that chronic exposure of human bronchial epithelial cells to As 3ϩ generates ROS and that ROS are responsible for As 3ϩ -induced transformation of these cells (16). In our present study, we have shown that As 3ϩ -transformed cells have a low level of ROS along with highly expressed antiapoptotic proteins (Bcl-2 and Bcl-xL) and antioxidant enzymes (catalase and SOD2) as well as Nrf2 and p62.…”
Section: Discussionmentioning
confidence: 99%
“…7G). As 3ϩ -induced ROS have been shown to have oncogenic properties in the premalignant stage; exposure of human lung bronchial epithelial cells to As 3ϩ generates ROS, which are responsible for malignant transformation of these cells (16). In this stage, the Nrf2 is inducible and is regulated by Keap1.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In accordance, proliferation of HaCaT cells were shown to be stimulated at low H 2 O 2 concentrations [35]. Our results correlate with other studies showing an association between low-concentrations of metals and stimulation of cell proliferation [36][37][38] and generation of ROS through NOX activation [39,40].…”
Section: Discussionsupporting
confidence: 91%
“…One mechanism involves the iAs-induced production of reactive oxygen species (ROS) which has been reported in multiple cell models including human lung bronchial epithelial BEAS-2B cells, human vascular smooth muscle cells, vascular endothelial cells, U937 cells, NB4 cells, human-hamster hybrid cells, CHO-K1 cells, and HEL30 cells (10)(11)(12)(13)(14)(15)(16). The impact of iAs on ROS production is hypothesized to occur in two steps.…”
Section: Proposed Mechanisms Of Ias-mediated Carcinogenesis and Toxicitymentioning
confidence: 99%